2015
DOI: 10.1007/s10806-015-9542-2
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthiness and Responsible Research and Innovation: The Case of the Bio-Economy

Abstract: The approach of responsible research and innovation (RRI) has been proposed to support the introduction of technologies that touch upon socially sensitive issues. RRI is intended to help designers and manufacturers of new technologies identify and accommodate public concerns when developing a new technology by engaging with a wide range of relevant actors in an interactive, transparent process. However what this approach amounts to exactly remains elusive as of yet, i.e. it is unclear what its contribution to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 18 publications
(21 reference statements)
0
44
0
1
Order By: Relevance
“…According to McCormick, a combination of consumer information that informs on the advantages of bio-based products and possibilities for participation by citizens and civil society organizations in the implementation process should be provided [109]. There are different proposals for achieving successful participation, such as the creation of transparency and equal levels of knowledge, building trust between stakeholders, a willingness to critically reflect opposing positions, and early conflict management (e.g., [34,110]). However, these approaches have not been implemented in the context of the bioeconomy up to now.…”
Section: Priority Setting In Research Funding and Involvement Of Stakmentioning
confidence: 99%
“…According to McCormick, a combination of consumer information that informs on the advantages of bio-based products and possibilities for participation by citizens and civil society organizations in the implementation process should be provided [109]. There are different proposals for achieving successful participation, such as the creation of transparency and equal levels of knowledge, building trust between stakeholders, a willingness to critically reflect opposing positions, and early conflict management (e.g., [34,110]). However, these approaches have not been implemented in the context of the bioeconomy up to now.…”
Section: Priority Setting In Research Funding and Involvement Of Stakmentioning
confidence: 99%
“…We chose the single case of Park Cuijk, which can be justified by the fact that our study has several elements of what Yin calls a 'revelatory case' ( [46], p. 40), meaning that the phenomenon investigated was previously inaccessible to scientific investigation. 2 An extensive literature review to justify a claim that our case is unique was beyond the scope of our study, but we know that the envisioned scheme for smart use of biomass in our case study is unprecedented in The Netherlands, as it probably also is in the European context, in terms of the number and the rich diversity of steps involved in cascaded biomass uses that are envisaged. No publications on similar case studies have been identified.…”
Section: Single Case Study Approachmentioning
confidence: 97%
“…5 Such inter-firm trust is always important for innovative projects, but for smart biomass use this is even more so, because it often requires cooperation outside traditional value chains; the aim is to have sectors cooperate that used to be strangers to one another. In an emerging bioeconomy context, the enhancement of such trusting relationships, on the institutional, organisational and personal levels, is important to get the ball rolling [2].…”
Section: Comparison With Acceptance Of Renewable Energy Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…A means to overcome these conflicts and consequent public distrust has been proposed through the approach of responsible research and innovation (RRI) (Asveld et al 2015). If implemented universally RRI should provide transparency and responsiveness, and is also aimed to enhance public trustworthiness in socially sensitive issues involving bioeconomy and other technologies.…”
Section: Environmental and Ecological Aspects In The Overall…mentioning
confidence: 99%